Trisomy 13 in monozygotic twins discordant for major congenital anomalies. Issue 8 (August 1987) - Naor, N; Amir, Y; Cohen, T; Davidson, S
Abstract : The occurrence of trisomy 13 in twins is very rare. We report a pair of genotypically identical twins with trisomy 13 discordant for major anomalies. This case contributes to the already published data on the contribution of non-genetic factors to the aetiology of congenital malformations in monozygotic twins.